Research Of The Physical Education Of Students Of The Military-Technical Lyceum "School Of Temurbeks" Taking Into Account The Influence Of Regional Factors (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article presents the results of a pedagogical experiment to identify the effectiveness of the developed accentuated program for improving the motor abilities of students of the military-technical lyceum in physical education classes, taking into account regional factors